Ligand-mediated electron transfer in pH-tolerant Mn(II)/Fe(VI) bimetallic system: High-valent iron-oxo generation for efficient antibiotic removal - Jia-Xuan Ou-Yang; Xin-Jia Chen; Yu-Kun Huang; Jia-He Guo; Pi-Jun Duan; Xin-Yi Zhang; Chang-Wei Bai; Zhi-Quan Zhang; Jing Wang; Ming-Jie Huang; Ying Shao; Xiao-Wei Xu; et al. (Water Research, 2027)

Making waves: Rethinking membrane technologies for water remediation from a full-chain application perspective - Jing Wang; Chang-Wei Bai; Xin-Jia Chen; Zhi-Quan Zhang; Yu-Kun Huang; Xiao-Wei Xu; Pi-Jun Duan; Jin-Song Guo; Fei Chen (Water Research, 2026)

Rapid and sensitive on-site detection of PBoV G3 using an EsCas13d-based platform - Peng-fei Fu; Zhuo-wei Zhang; Jun Hong; An-xin Hu; Yi-yang Shi; Jia-wen Lin; Si-yi Pi; Yu-yan Zhang; Yan-hong Wang; Min Lu; Guo-you Yin; Dong-mei Wang (Analytica Chimica Acta, 2026)

In vitro regeneration via indirect organogenesis from aseptic seedling-derived explants of the rare Tibetan medicinal shrub Sibiraea angustata - Mengting Pi; Xue Yu; Hongchang Li; Yali Guo; Wuyang Lai; Leipeng Cao; Tao Jiang; Lingxia Xu; Fuhua Peng; Hongdong Liu; Fei Wang; Jianguo Hu; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Paleoproterozoic Dongyaozhuang orogenic gold deposit in the Trans-North China Orogen: Constraints from in-situ U-Th-Pb dating of hydrothermal monazite and trace elements and sulfur isotopes of sulfides - Ying Ma; Shao-Yong Jiang; Ning Jin; Dao-Hui Pi; Yu Jiang; Guo-Hai Guo (Precambrian Research, 2026)

Closed-loop photothermal extraction and catalytic degradation for remediation of phenol-contaminated soil - Jian Zhang; Huimin Yu; Xiong Yang; Yafei Shi; Yi Lu; Gary Owens; Tiantian Deng; Kewu Pi; Pan Wu (Journal of Hazardous Materials, 2026)

New insight into the role of lipids in the formation and retention of key aroma compounds in micro-pressure stewed beef based on lipidomics and lipid-derived free radical analysis - Huan Liu; Yu Liu; Xinhe Zhang; Bo Xiao; Pi Li; Peng Gao; Jiangtao Xing; Weiting Wang; Pengfei Du; Jingxian Cong; Chengyu Zeng; Cheng Li; et al. (Food Research International, 2026)

Analysis and identification of geographical indication protected Huangjiu based on multimodal data combined with chemometric methods - Xiaodan Liu; Qiuwen Shan; Xianhao Ding; Chao Ji; Yonghui Yu; Huang Dai; Fuwei Pi; Jiahua Wang; Ming Zhang (Food Control, 2026)

Solar-driven rooftop interfacial evaporation system for decentralized rainwater purification - Liang Hu; Huimin Yu; Xiong Yang; Shulian Wang; Yafei Shi; Zhu Li; Kewu Pi; Gary Owens; Pan Wu (Water Research, 2026)

Buffer-free BOZn coordination sites enable efficient Fe(VI) oxidation for organic pollutant removal - Xin-Jia Chen; Yu-Kun Huang; Ning Li; Pi-Jun Duan; Chang-Wei Bai; Zhi-Quan Zhang; Jing Wang; Ying Shao; Xiao-Wei Xu; Jin-Song Guo; Fei Chen (Chemical Engineering Journal, 2026)

Bioinspired self-assembled gradient Janus bilayer aerogel enabling coupled solar desalination and purification of multicomponent oily emulsions - Peng Pi; Yu Feng; Wen Jung Li; Ling Pan; Youxi Lin; Linxi Hou; Zihao Huang; Qinwei Wang; Xuhui Wang; Zhiying Ren (Chemical Engineering Journal, 2026)

Triggering mechanisms of the 2024 M4.5 earthquake swarm in Mozhugongka, Tibetan Plateau: Constraints from seismotectonics and the role of deep fluids - Guoqiang Ji; Xingzhong Du; Yong Li; Xuan Ke; Xiaohui Hu; Huabiao Liu; Yu Tang; Kairong Pi (Journal of Seismology, 2026)

Comprehensive multi-omics analysis reveals key metabolites and lipids driving flavor development in quail egg yolk - Cui Ma; Xiaoyue Yu; Hao Zhang; Yuejin Pu; Jinsong Pi; Yan Wu (Food Chemistry, 2026)

The inhibition of the AMPK and PPAR signaling pathways may be involved in the metabolic disorder of large yellow croaker induced by Pseudomonas plecoglossicida ppTse6 - Huan-jiao Tan; Yu-jia Sun; Xi-zhi Peng; Qing-pi Yan (Fish & Shellfish Immunology, 2026)

Acetyl-CoA synthetase 2 nuclear translocation impediment contributes to nickel induced histone hypoacetylation and neurite outgrowth impairment - Chao Zhou; Jianbo Zhang; Wenjuan Zhang; Ya Xu; Xiang Mei; Ping Deng; Qinlong Ma; Chunhai Chen; Lei Zhang; Huifeng Pi; Zhou Zhou; Zhengping Yu; et al. (Toxicology Letters, 2026)

Insights into the effects of ultrasound on the structural, aggregation behavior, and functional properties of almond isolate protein: An integrated experimental and molecular dynamics simulation studies - Yu-Hang Jiang; Pi-Miao Huang; Yang-You Li; Yu-Ting Zhao; Yue Zheng; Yu-Xing Zhou; Wei-Gang Xin; Hua-Yi Suo (Food Research International, 2026)

Harnessing dual-stable conformers in o-carborane-based multi-resonance emitters for achieving single-emitter white OLEDs - Zezhu Xiao; Chen-Yu Lin; Jianxing Chen; Songqian Ni; Xingtian Wang; Ming-Yu Teng; Weiguo Zhu; Pi-Tai Chou; Xiugang Wu (Chemical Engineering Journal, 2026)

Nitrogen doped graphene quantum dots modified a crystalline zinc phosphite based non-enzymatic electrochemical sensor for the ultra-low detection of tyramine - Pi-Chen Wei; Asit Kumar Panda; Yu-Chung Chang; Yi-Rong Li; Todd Hsu; Chih-Min Wang (Food Control, 2026)

Study and application of energy-dissipating yielding support for large deformation in hard rock tunnel subjected to extremely high geostress - Sheng Pi; Mingnian Wang; Xun Luo; Li Yu; Youlin Qin (Tunnelling and Underground Space Technology, 2026)

Dual-path synergistic mechanism of coal spontaneous combustion based on the multi-scale characterization of the activation energy - Yong Chen; Yulong Zhang; Yu-long Zhang; Pi Lu; Junfeng Wang; Chunshan Zhou (Fuel, 2026)

Catalytic hairpin assembly-assisted dual-enhanced SERS satellite nanocomplex for ultrasensitive detection of lipopolysaccharides in injection samples - Chan Huang; Xiuying Li; Xuan Zeng; Lingzhi Chen; Huabin Zhang; Xinjie Guo; Yiqun Chang; Wenshi Huang; Yichu Nie; Tianen Zhou; Jiaqi Yu; Jun Xu; et al. (Chemical Engineering Journal, 2026)

Impacts of cold spells on mortality risk in low-latitude subtropical plateau regions: a multi-dimensional analysis of spatial heterogeneity and vulnerability in Yunnan Province, China - Le-Yun Tan; Xian Tang; Yu-Hui Chen; Yang Chen; Qiu-Li Yu; Yuan-Yi Zha; Pi Guo; Qing-Ying Zhang (International Journal of Biometeorology, 2026)

Metacontrol-related aperiodic and periodic neural activity in cognitive aging: enhancing the neural signal-to-noise ratio through anodal transcranial direct current stimulation - Yu Pi; Qinfei Zhang; Shuhui Lyu; Christian Beste; Lorenza Colzato; Bernhard Hommel (GeroScience, 2026)
Metacontrol, the ability to adapt cognitive control to task demands, declines with age and is thought to be reflected in aperiodic and periodic neural dynamics. Given that anodal transcranial direct current stimulation (atDCS) can modulate cortical excitability via membrane potential shifts, we tested whether atDCS alters the neurophysiological signatures of metacontrol in younger and older adults. In a mixed design, younger and older participants performed a Go/Nogo task under both atDCS and sham stimulation conditions; resting-state EEG data were also acquired. Aperiodic activity was analyzed using the FOOOF algorithm, and periodic activity was examined through time–frequency analysis. Behaviorally, younger adults showed higher accuracy and faster responses than older adults, but no significant stimulation effects emerged in either group. Results showed that, compared to sham, aperiodic activity (FOOOF exponent) increased after atDCS, particularly in older adults, indicating a steepening of the EEG spectrum and thus increased inhibitory tone in the aging process. However, resting-state aperiodic activity did not predict stimulation-induced effects within either group. In the periodic domain, we found no evidence that atDCS modulated task-related theta or alpha power. Moreover, exploratory analyses revealed no significant associations between atDCS-induced changes in the aperiodic exponent and oscillatory power. This dissociation indicates that, under the present conditions, the periodic and aperiodic components of the EEG signal reflect distinct and likely independent neurophysiological responses to neuromodulation. Targeting metacontrol mechanisms through neuromodulation may, with further validation, open new avenues for supporting cognitive health in older adults. Graphical Abstract

Effect of Guide Slot on Fracture Propagation Under the Expansion Pressure of Static Chemical Agents - Wei Tang; Cheng Zhai; Ning Luo; Jizhao Xu; Yangfeng Zheng; Wang Yu; Chengjian Pi (Rock Mechanics and Rock Engineering, 2026)

Solar evaporation-driven integrated system for saline soil remediation, freshwater recovery, salt resource harvest, and agricultural irrigation - Huimin Yu; Liang Hu; Pan Wu; Xiong Yang; Yafei Shi; Zhu Li; Kewu Pi (Water Research, 2025)

CYP450 activation and mitophagy induction mediate Ti3C2 MXene detoxification in RAW 264.7 cells - Yujiao Liu; Xuan Mao; Yongyi Wei; Xiaodi Li; Jianbo Jia; Qingmeng Liu; Jian Liu; Yu Wang; Xiaofei Zhou; Huihui Wang; Jingbo Pi; Guangbo Qu; et al. (Journal of Hazardous Materials, 2025)

Hydrogeochemical characteristics and the monitoring from 2020 to 2023 of hot spring waters in Tatun Volcanic Group, Taiwan - Ju-lien Pi; Hsueh-Yu Lu; Hsiao-Fen Lee; Hung-Chun Chao; Chen-Feng You; Tsung-Ren Peng; Raymond Patrick R. Maximo; Chia-Tai Wu; Ya-Wen Wu; Chung Fang; Cheng-Horng Lin (Journal of Asian Earth Sciences, 2025)

Synergistic and continuous driving of Fe(III)/Fe(II) cycle by electron-rich organic contaminants and peroxymonosulfate: Homogeneous feasibility and heterogeneous application - Jin Chai; Yu Wei; Haoran Kong; Hui Liu; Zhuohan Li; Junshuo Huang; Ruobing Pi; Zhe Yang; Xuhui Sun (Chemical Engineering Journal, 2025)

The electric double layer governs the spatially-variable thermodynamic equilibrium of gas hydrates in clays - Sheng-Li Li; Yu-Xiang Chen; John J. Carroll; Shu-Hui Jiang; Pi-Bo Su (Chemical Engineering Journal, 2025)

Manganese oxides for electrochemical adsorption of metal ions in aqueous environments: A comprehensive review from fundamentals to applications - Xiong Yang; Jiahai Yu; Yafei Shi; Kewu Pi; Chengshuai Liu; Guohong Qiu (Critical Reviews in Environmental Science and Technology, 2025)

Investigating the protective role of Astragalus polysaccharides against fluoride-induced testicular injury via network pharmacology, molecular docking, and in vivo experiments - Yue Pan; Xingyan Du; Yuanyuan Xiao; Qiuhan Pi; Yu Chen; Jiajun Huang; Didong Lou; Wenchao Tang (Reproductive Toxicology, 2025)

Exploring the anticancer potential of Polygonum barbatum (L.) against colorectal cancer: In vitro and in vivo investigations - Pi-Kai Chang; I-Chuan Yen; Wei-Cheng Tsai; Kuen-Tze Lin; Shih-Yu Lee (Phytochemistry Letters, 2025)

Immunosuppressive role of benzo[a]pyrene exposure in prostate cancer progression - Zhijin Zhang; Wentao Zhang; Huan Wang; Haotian Chen; Hong Wang; Yang Yu; Danjing Shen; Man Pi; Yang Wu; Ming Luo; Yanyan He; Shiyu Mao; et al. (Journal of Environmental Sciences, 2025)

Sensitive dual detection of N-nitrosodiphenylamine and N-nitrosodiethylamine using a PtNPs-enhanced MWCNTs/Fe-porphyrinic MOF nanocomposite-based electrochemical sensor - Jiachen Zhao; Yue Zou; Junlan Yu; Chao Wang; Yili Hu; Fangkai Han; Ning Yang; Fuwei Pi; Ming Zhang; Xiaodan Liu; Jiahua Wang; Huang Dai; et al. (Food Chemistry, 2025)

Lignin-derived biochar for high-performance electrochemical adsorption of Cd(II) from aqueous solutions - Jiahai Yu; Xiong Yang; Lei Xiao; Shizhu Song; Jiayue Chen; Liwen Cao; Min Xia; Pan Wu; Kewu Pi; Guohong Qiu (Journal of Water Process Engineering, 2025)

NtLYK5 negatively regulates drought resistance in tobacco through H2O2-mediated leaf stomatal opening and closing - Yonglu Xue; Qiwei Yu; Gang Chen; Zhenbao Luo; Kai Pi; Baolin Xie; Kaiping Wu; Chenhao Shi; Renxiang Liu (Plant Cell Reports, 2025)

Inversion of Rayleigh wave dispersion curves based on the Osprey Optimization Algorithm - Zhi Li; Hang-yu Yue; De-xi Ma; Yu Fu; Jing-yang Ni; Jin-jun Pi (Applied Geophysics, 2025)

Photothermal evaporation and intelligent drip irrigation for efficient water recycling during closed-loop saline soil remediation - Huimin Yu; Pan Wu; Jiayi Wang; Xiong Yang; Yafei Shi; Zhu Li; Gary Owens; Kewu Pi (Chemical Engineering Journal, 2025)

Physiological functions of the transcription factor GmZAT10-1 gene involved in the salt stress adaptation in soybean - Tianlei Zhang; Li Yu; Yutin Chen; Yi Zeng; Boyi Pi; Xun Liu; Bingjun Yu (Plant Science, 2025)

Aptamer-modulated Pt/Au/MIL-100(Fe) nanozymatic activity for the colorimetric detection of deoxynivalenol in grains - Huang Dai; Junlan Yu; Run Zhou; Guijie Hao; Zhaohui Qiao; Zhe Feng; Xin Liu; Jie Bi; Jiahua Wang; Xiaodan Liu; Fuwei Pi; Yafang Shen (Food Chemistry, 2025)

A tongue resistance training program improves strength, endurance, and swallowing in frail older adults with mild cognitive impairment: a double-blind randomized controlled trial - Shu-Hua Kao; Ruey Chen; Pi-Yu Su; Kondwani Joseph Banda; Chien-Mei Sung; Chia-Hui Wang; Kai-Jo Chiang; Melati Fajarini; Kuei-Ru Chou (GeroScience, 2025)

3D self-supportive structures of micro/nanofiber assemblies constructed in situ in air turbulent flow fields for thermal protection at extreme conditions - Pi-Hang Yu; Yuan Gao; Guo-Dong Zhang; Chao Zhang; Chuan-Hui Guo; Seeram Ramakrishna; Yun-Ze Long; Jun Zhang (Chemical Engineering Journal, 2025)

Nrf2 deficiency aggravates hepatic cadmium accumulation, inflammatory response and subsequent injury induced by chronic cadmium exposure in mice - Chengjie Chen; Xue Han; Ning Xu; Wei Shen; Gang Wang; Junying Jiao; Weiwei Kong; Jiaxin Yu; Jingqi Fu; Jingbo Pi (Toxicology and Applied Pharmacology, 2025)

Continuous treatment of contaminants through activation of peroxymonosulfate utilizing ferrate-modified graphite felt: Radical and non-radical - Zhe Yang; Jin Chai; Yu Wei; Ruobing Pi; Siyang Wang; Xuhui Sun (Journal of Water Process Engineering, 2025)

A reversible solar photothermal Li-CO2 battery enabled by engineering 3D plasmonic Cr-N-Ru catalysts assembled on carbon-free Si NP cathode - Shimin Chen; Junnan Han; Zhihuan Li; Zijie Lin; Min Wang; Hucheng Song; Xiaodong Pi; Dongke Li; Linwei Yu; Jun Xu; Kunji Chen (Chemical Engineering Journal, 2025)

Replication factor C4, which is regulated by insulin-like growth factor 2 mRNA binding protein 2, enhances the radioresistance of breast cancer by promoting the stemness of tumor cells - Xiao-Yu Zhu; Pi-Song Li; Hui Qu; Xing Ai; Zi-Ting Zhao; Jia-Bei He (Human Cell, 2025)

Regulation of PPARγ in the development of early sheep embryos in vitro - Hengbin Yu; Chang Liu; Yue Zhang; Zhenghang Li; Wenhui Pi; Guangdong Hu (Theriogenology, 2025)

Aflatoxin B1 exposure induces Alzheimer's disease like pathology by disrupting redox homeostasis and activating ferroptotic signals in C57BL/6 J mice - Jinxian Lin; Huihui Hong; Sicheng Liu; Zhengwei Liang; Qixue Zheng; Kun Luo; Jiayi Li; Zhulin Du; Jinping Yu; Lingling Yang; Ping Deng; Huifeng Pi; et al. (Science of The Total Environment, 2025)

Safety and antioxidant assessments of BLR-E50, 50% ethanolic extract from red beans co-fermented by Bacillus subtilis and Lactobacillus bulgaricus - Su-Tze Chou; Yi-Hua Chen; Yi-Hung Chen; Yu‐Chen Tsai; Yun-Chin Chung; Ju-Pi Li (Food and Chemical Toxicology, 2025)

Possible Mechanisms Underlying the Postharvest Increased Abscission of Seeded Table Grape After Seedless-Inducing Treatment - Jun Yu; Shuiqin Pi; Linfeng Kang; Qian Tan; Mingtao Zhu (Journal of Plant Growth Regulation, 2025)

Composition, structure and comprehensive utilization of abalone shell: A review - Man-Yu Li; Yan-Chao Wu; Li Huang; Pi-Xian Gong; Hui-Jing Li (Sustainable Chemistry and Pharmacy, 2025)

Where and why do Mei-yu season Heavy-rainfall quantitative precipitation forecasts in Taiwan improve the most using a higher model resolution - Chung-Chieh Wang; Pi-Yu Chuang; Kazuhisa Tsuboki (Natural Hazards, 2025)

Combined Remediation Effects of Sewage Sludge and Phosphate Fertilizer on Pb-Polluted Soil from a Pb-Acid Battery Plant - Ting Zhang; Xiong Yang; Zhijia Zeng; Qiang Li; Jiahai Yu; Huiling Deng; Yafei Shi; Huiqin Zhang; Andrea R. Gerson; Kewu Pi (Environmental Management, 2024)

Correction to: Effects of Long-term Climate Change on Typhoon Rainfall Associated with Southwesterly Monsoon Flow near Taiwan: Mindulle (2004) and Morakot (2009) - Chung-Chieh Wang; Li-Shan Tseng; Chien-Chang Huang; Pi-Yu Chuang; Nan-Chou Su; Cheng-Ta Chen; Shih-How Lo; Kazuhisa Tsuboki (Asia-Pacific Journal of Atmospheric Sciences, 2024)

Effects of dietary supplementation with fermented flaxseed meal on the growth performance, immune function, and intestinal microbiota of growing pigs - Lei Xu; Zixi Wei; Yao Guo; Baozhu Guo; Long Cai; Jingjiao Yan; Lianghua Ma; Wenjuan Sun; Yanpin Li; Xianren Jiang; Xilong Li; Yu Pi (Animal Feed Science and Technology, 2024)

WUSCHEL RELATED HOMEOBOX5 and 7 maintain callus development by promoting cell division in Arabidopsis - Yi Yang; Caifeng Liu; Yue Yu; Guiping Ran; Ning Zhai; Limin Pi (Plant Science, 2024)

Polyphenol (−)-Epigallocatechin Gallate (EGCG) mitigated kidney injury by regulating metabolic homeostasis and mitochondrial dynamics involvement with Drp1-mediated mitochondrial fission in mice - Yue-Lei Chu; Jin-Chan Pi; Yu-Fei Yao; Xuan-Ying Chen; Xiao-Ping Peng; Wen-Juan Li (Food and Chemical Toxicology, 2024)

Paraquat disrupts KIF5A-mediated axonal mitochondrial transport in midbrain neurons and its antagonism by melatonin - Huihui Hong; Jingdian Li; Tong Tong; Ting Yang; Hui Wang; Yudong Xu; Xiqin Lin; Jinxian Lin; Sicheng Liu; Kun Luo; Zhengping Yu; Wei Yuan; et al. (Science of The Total Environment, 2024)

Volcanic lithofacies control the space in unconventional, rhyolitic hydrocarbon reservoirs: The Hailar Basin, NE China - Yuting Chen; Han Zheng; Guido Ventura; Linlin Zeng; Wei Pi; Yu Wei (Marine and Petroleum Geology, 2024)

Stem Cell Therapy in Neonatal Hypoxic-Ischemic Encephalopathy and Cerebral Palsy: a Bibliometric Analysis and New Strategy - Qiu-Xia Xiao; Min-Jian Geng; Yi-Fei Sun; Yu Pi; Liu-Lin Xiong (Molecular Neurobiology, 2024)

Nucleic acid amplification-based strategy to detect foodborne pathogens in milk: a review - Lidong Pang; Xiaowen Pi; Xinyan Yang; Danliangmin Song; Xue Qin; Lihan Wang; Chaoxin Man; Yu Zhang; Yujun Jiang (Critical Reviews in Food Science and Nutrition, 2024)

Influence of gestational hypertension and maternal air pollutant exposure on birth outcomes - Tai-Ho Hung; Te-Yao Hsu; Jie Hsu; Chia-Yu Ou; Pi-Hua Liu; Liang-Ming Lo; Steven W Shaw; Gwo-Hwa Wan (Environmental Science and Pollution Research, 2024)

Effects of Long-term Climate Change on Typhoon Rainfall Associated with Southwesterly Monsoon Flow near Taiwan: Mindulle (2004) and Morakot (2009) - Chung-Chieh Wang; Li-Shan Tseng; Chien-Chang Huang; Pi-Yu Chuang; Nan-Chou Su; Cheng-Ta Chen; Shih-How Lo; Kazuhisa Tsuboki (Asia-Pacific Journal of Atmospheric Sciences, 2024)

Electrochemical reductive removal of trichloroacetic acids by a three-dimensional binderless carbon nanotubes/ CoP/Co foam electrode: Performance and mechanism - Li He; Fubing Yao; Yu Zhong; Chang Tan; Shengjie Chen; Zhoujie Pi; Xiaoming Li; Qi Yang (Journal of Hazardous Materials, 2024)

Long-term cadmium exposure induces epithelial-mesenchymal transition in breast cancer cells by activating CYP1B1-mediated glutamine metabolic reprogramming in BT474 cells and MMTV-Erbb2 mice - Jingdian Li; Peng Gao; Mingke Qin; Junhua Wang; Yan Luo; Ping Deng; Rongrong Hao; Lei Zhang; Mindi He; Chunhai Chen; Yonghui Lu; Qinlong Ma; et al. (Science of The Total Environment, 2024)

Biophysical mechanisms underlying tefluthrin-induced modulation of gating changes and resurgent current generation in the human Nav1.4 channel - Hsing-Jung Lai; Ming-Jen Lee; Hsin-Wei Yu; Kuan-Wen Chen; Ke-Li Tsai; Pi-Chen Lin; Chiung-Wei Huang (Pesticide Biochemistry and Physiology, 2024)

A fluorescence and SERS dual-mode sensing on tetracycline antibiotics based on Ag@NH2-MIL-101(Al) nanoprobe - Junjie Qi; Jingkun Li; Yuqi Wan; Yu Li; Fuwei Pi (Food Chemistry, 2024)

Ganoderma spp. polysaccharides are potential prebiotics: a review - Miao Zheng; Xiaowen Pi; Hongxuan Li; Shasha Cheng; Yue Su; Yu Zhang; Chaoxin Man; Yujun Jiang (Critical Reviews in Food Science and Nutrition, 2024)

Gaussian meta-feature balanced aggregation for few-shot synthetic aperture radar target detection - Zheng Zhou; Zongyong Cui; Kailing Tang; Yu Tian; Yiming Pi; Zongjie Cao (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Transparent self-cleaning coatings repellent to ultralow surface tension liquids in extreme environments - Liying Liu; Min Zhang; Yuanyang Yan; Yahong Zhou; Shuangfeng Wang; Pihui Pi; Xiufang Wen; Yu Qian; Lei Jiang (Chemical Engineering Journal, 2024)

Solution chemistry strategies to construct a stable MAPbI3 film toward high performance of amplified spontaneous emission - Haoyue Luo; Mingyu Pi; Zijun Zhan; Nian Liu; Xin Zeng; Jie Zeng; Yuan Xiang; Xinyi Kuang; Yexiong Huang; Juan Du; Dingke Zhang; Zhengzheng Liu; et al. (Chemical Engineering Journal, 2024)

Hit two birds with one stone: A bi-functional selenium-substituted organosulfur polymer additive for high-performance lithium-sulfur batteries - Yu Ding; Xiang Li; Yiming Chen; Yuqiang Pi; Jiage Yu; Lixia Yuan; Feng Wang (Chemical Engineering Journal, 2024)

Progress on aptamer-based SERS sensors for food safety and quality assessment: methodology, current applications and future trends - Guoyong Jiang; Yu Li; Jinghan Liu; Ling Liu; Fuwei Pi (Critical Reviews in Food Science and Nutrition, 2024)

Long-term exposure to polystyrene microplastics induces hepatotoxicity by altering lipid signatures in C57BL/6J mice - Jiawen Tao; Ping Deng; Min Lin; Chunhai Chen; Qinlong Ma; Lingling Yang; Wenjuan Zhang; Yan Luo; Siyu Chen; Huifeng Pi; Zhou Zhou; Zhengping Yu (Chemosphere, 2024)

In situ Raman characterization of the stability of blueberry anthocyanins in aqueous solutions under perturbations in temperature, UV, pH - Chuchu Duan; Xiaofeng Xiao; Yonghui Yu; Mengting Xu; Yanpeng Zhang; Xiaodan Liu; Huang Dai; Fuwei Pi; Jiahua Wang (Food Chemistry, 2024)

Bacterial, short-chain fatty acid and gas profiles of partially hydrolyzed guar gum in vitro fermentation by human fecal microbiota - Xiong-E Pi; Hao Fu; Xiao-Xia Yang; Zai-Chun Yu; Wei-Lin Teng; Yinjun Zhang; Xue-Wei Ye; Hui Hui Quan; Li-Zhi Lu; Wei Liu (Food Chemistry, 2024)

Chronic cadmium exposure triggered ferroptosis by perturbing the STEAP3-mediated glutathione redox balance linked to altered metabolomic signatures in humans - Ping Deng; Jingdian Li; Yonghui Lu; Rongrong Hao; Mindi He; Min Li; Miduo Tan; Peng Gao; Liting Wang; Huihui Hong; Jiawen Tao; Muxue Lu; et al. (Science of The Total Environment, 2023)

Comparison of high-hydrostatic pressure and frozen treatments on raw freshwater clam marinated in soy sauce: Impact on microbiological and organoleptic qualities - Pi-Chen Wei; Yi-Chen Lee; Yu-Chi Chen; Chung-Saint Lin; Po-Wei Chen; Todd Hsu; Yung-Hsiang Tsai (Food Control, 2023)

Environmental cadmium exposure facilitates mammary tumorigenesis via reprogramming gut microbiota-mediated glutamine metabolism in MMTV-Erbb2 mice - Yang Yue; Huadong Zhang; Ping Deng; Miduo Tan; Chengzhi Chen; Bo Tang; Jingdian Li; Fengqiong Chen; Qi Zhao; Ling Li; Rongrong Hao; Hui Wang; et al. (Science of The Total Environment, 2023)

Chronic cadmium exposure induces Parkinson-like syndrome by eliciting sphingolipid disturbance and neuroinflammation in the midbrain of C57BL/6J mice - Yudong Xu; Huihui Hong; Xiqin Lin; Tong Tong; Jingjing Zhang; Haotian He; Lingling Yang; Gaofeng Mao; Rongrong Hao; Ping Deng; Zhengping Yu; Huifeng Pi; et al. (Environmental Pollution, 2023)

Corrigendum to “PKC-δ-dependent mitochondrial ROS attenuation is involved as 9-OAHSA combats lipoapotosis in rat hepatocytes induced by palmitic acid and in Syrian hamsters induced by high-fat high-cholesterol high-fructose diet” [Toxicology and Applied Pharmacology, 470, (2023), 116557] - Ching-Hui Loh; Wei-Wen Kuo; Shinn-Zong Lin; Cheng-Yen Shih; Pi-Yu Lin; Jiro Hasegawa Situmorang; Chih-Yang Huang (Toxicology and Applied Pharmacology, 2023)

Gain-of-function allele of HPY1 coordinates source and sink to increase grain yield in rice - Fengfeng Fan; Manman Liu; Nannan Li; Yu Guo; Huanran Yuan; Fengfeng Si; Mingxing Cheng; Gaili Chen; Meng Cai; Nengwu Li; Yixin Zhang; Yi Yu; et al. (Science Bulletin, 2023)

Sperm quality decline associated with gaseous pollutant exposure: Evidence from a large cohort multicenter study - Xiaoyan Cai; Haobo Ni; Qiling Wang; Tingting Dai; Lingxi Wang; Chunying Song; Yushan Li; Fuping Li; Tianqing Meng; Huiqiang Sheng; Lina Xiao; Ting Xu; et al. (Journal of Hazardous Materials, 2023)

An interfacial solar evaporation enabled autonomous double-layered vertical floating solar sea farm - Pan Wu; Xuan Wu; Huimin Yu; Jingyuan Zhao; Yida Wang; Kewu Pi; Gary Owens; Haolan Xu (Chemical Engineering Journal, 2023)

Insight into nanomaterials mediated dual-modal assay for food safety: Design principles and applications - Gengli Huang; Xueli Luo; Guoyong Jiang; Yu Li; Sa-adu Abiola Dauda; Jiayi Li; Fuwei Pi (Trends in Food Science & Technology, 2023)

Nrf2 protects against renal fibrosis induced by chronic cadmium exposure in mice - Chengjie Chen; Zhengsheng Zhou; Siqi Yu; Yawei Ma; Gang Wang; Xue Han; Congcong Jiao; Junjun Luan; Zhiyuan Liu; Yuanyuan Xu; Huihui Wang; Qiang Zhang; et al. (Food and Chemical Toxicology, 2023)

Transcriptomics integrated with metabolomics unravels the interweaving of inflammatory response and 1-stearoyl-2-arachidonoyl-sn-glycerol metabolic disorder in chronic cadmium exposure-induced hepatotoxicity - Rongrong Hao; Heng Xiao; Hui Wang; Ping Deng; Yang Yue; Jingdian Li; Yan Luo; Li Tian; Jia Xie; Mengyan Chen; Zhou Zhou; Fengqiong Chen; et al. (Environmental Toxicology and Pharmacology, 2023)

Identification of RPD3/HDA1 Family Genes in Sugar Beet and Response to Abiotic Stresses - Qingyang Yu; Qianting Guo; Baizheng Li; Xiangxiao Tan; Liumin Wang; Shengnan Li; Zhi Pi (Sugar Tech, 2023)

PKC-δ-dependent mitochondrial ROS attenuation is involved as 9-OAHSA combats lipoapotosis in rat hepatocytes induced by palmitic acid and in Syrian hamsters induced by high-fat high-cholesterol high-fructose diet - Ching-Hui Loh; Wei-Wen Kuo; Shinn-Zong Lin; Cheng-Yen Shih; Pi-Yu Lin; Jiro Hasegawa Situmorang; Chih-Yang Huang (Toxicology and Applied Pharmacology, 2023)

Solar-Driven interfacial evaporation for decentralized direct potable reuse of domestic wastewater - Weixiang Chao; Shanshan Pi; Yang Yang; Zhida Li; Yongjie Yu; Ying Yang; Ruijie Yang; Haiyan Li; Lu Lu (Chemical Engineering Journal, 2023)

Wide-Scope Multi-residue analysis of pesticides in beef by gas chromatography coupled with quadrupole Orbitrap mass spectrometry - Xu Pang; Jing Qiu; Zhaoyang Zhang; Pi Li; Jiangtao Xing; Xin Su; Guiqiao Liu; Changyuan Yu; Rui Weng (Food Chemistry, 2023)

Fabrication of foxtail millet prolamin/caseinate/chitosan hydrochloride composite nanoparticles using antisolvent and pH-driven methods for curcumin delivery - Xiao Chen; Yan-Chao Wu; Liu-Hong Qian; Yu-He Zhang; Pi-Xian Gong; Wei Liu; Hui-Jing Li (Food Chemistry, 2023)

The size of the susceptible pool differentiates climate effects on seasonal epidemics of bacillary dysentery - Haobo Ni; Qinghui Zeng; Ting Xu; Lina Xiao; Xiaolin Yu; Jinrui Hu; Yang Li; Hualiang Lin; Pi Guo; Haijian Zhou (Science of The Total Environment, 2023)

Long-term cadmium exposure impairs cognitive function by activating lnc-Gm10532/m6A/FIS1 axis-mediated mitochondrial fission and dysfunction - Ping Deng; Huadong Zhang; Liting Wang; Sheng Jie; Qi Zhao; Fengqiong Chen; Yang Yue; Hui Wang; Li Tian; Jia Xie; Mengyan Chen; Yan Luo; et al. (Science of The Total Environment, 2023)

Baicalin-berberine complex nanocrystals orally promote the co-absorption of two components - Ziwei Li; Yiting Liu; Jilin Wang; Xiaojiao Feng; Ebuka-Olisaemeka Nwafor; Ying Zhang; Rui Liu; Wenli Dang; Qingqing Zhang; Changxiang Yu; Jiaxin Pi; Zhidong Liu (Drug Delivery and Translational Research, 2022)

Correction to: LncRNA GATA3‑AS1 promoted invasion and migration in human endometrial carcinoma by regulating the miR‑361/ARRB2 axis - Yu‑xi Liu; Shuo Yuan; Xiao‑jing Liu; Yan‑xi Huang; Pin Qiu; Jie Gao; Gao‑pi Deng (Journal of Molecular Medicine, 2022)

Numerical Simulation on Dynamic Characteristics of Longitudinal Launching of Large Container Ships - Kaihua Liu; Yu Wang; Zhifei Wu; Juntao Pi; Wie Min Gho; Bo Zhou (Journal of Marine Science and Engineering, 2022)
The upsizing and rapid development of container ships has resulted in many large ships launching in small slipways due to the lagging of advanced equipment. In particular, the dynamic characteristics of these large ships in the longitudinal launching operation under restricted water are yet to be studied in detail. In this study, a ship model to simulate the longitudinal launching process of an 8500 TEU container ship was created based on the URANS method. The ship resistance in calm water was determined and validated against the experimental data. The influence of the stern appendage on the ship’s resistance and the flow field around the hull, with and without the aft poppet, under various water-depth-to-draught ratios was analyzed. A comparison of the ship’s resistance between the numerical and the experimental data shows that the difference is minimal, within 1.5%. The numerical results revealed that the aft poppets change the flow pattern and effectively reduce the pressure drag in the drifting stage. The shallow water causes a restraining effect on the ship. The proposed analytical approach in the numerical analysis, considering the aft poppet and the water depth, could provide a better simulation for a large ship’s longitudinal launching operation.

Correction to: LncRNA GATA3‑AS1 promoted invasion and migration in human endometrial carcinoma by regulating the miR‑361/ARRB2 axis - Yu‑xi Liu; Shuo Yuan; Xiao‑jing Liu; Yan‑xi Huang; Pin Qiu; Jie Gao; Gao‑pi Deng (Journal of Molecular Medicine, 2022)

LncRNA GATA3-AS1 promoted invasion and migration in human endometrial carcinoma by regulating the miR-361/ARRB2 axis - Yu-xi Liu; Shuo Yuan; Xiao-jing Liu; Yan-xi Huang; Pin Qiu; Jie Gao; Gao-pi Deng (Journal of Molecular Medicine, 2022)

Adaptation responses of microalgal-bacterial granular sludge to polystyrene microplastic particles in municipal wastewater - Huan Hou; Shulian Wang; Bin Ji; Yu Zhang; Kewu Pi; Yafei Shi (Environmental Science and Pollution Research, 2022)

Associations between ambient heat exposure early in pregnancy and risk of congenital heart defects: a large population-based study - Xiaolin Yu; Huazhang Miao; Qinghui Zeng; Haisheng Wu; Yuliang Chen; Pi Guo; Yingxian Zhu (Environmental Science and Pollution Research, 2022)

Phylogenetic and codon usage analysis for replicase and capsid genes of porcine circovirus 3 - Xianglong Yu; Kuipeng Gao; Molin Pi; Huizi Li; Wenxia Zhong; Baojian Li; Zhangyong Ning (Veterinary Research Communications, 2021)

A comparison of atmospheric geochemistry through lichens from volcanic and non-volcanic areas, north Taiwan - Le-Qi Lin; Hsueh-Yu Lu; Ju-Lien Pi; Tai-Sheng Liou; Wen-Fu Chen; Pei-Shan Hsieh (Journal of Earth System Science, 2021)

Three-dimensional Spheroid Culture Enhances Multipotent Differentiation and Stemness Capacities of Human Dental Pulp‐derived Mesenchymal Stem Cells by Modulating MAPK and NF-kB Signaling Pathways - Ya-Hui Chan; Yu-Chieh Lee; Chia-Yi Hung; Pi-Ju Yang; Pin-Chuang Lai; Sheng-Wei Feng (Stem Cell Reviews and Reports, 2021)

Drought tolerance in high-generation transgenic maize inbred lines overexpressing the betaine aldehyde dehydrogenase gene - He Zhao; Qi Zhang; Mo Zhang; Yu-Kun Jin; Zhen-Zhong Jiang; Nan Jiang; Qi Wang; Jing Qu; Shu-Yan Guan; Pi-Wu Wang (Cereal Research Communications, 2021)

Germination dynamics of allergenic fungal spores in respiratory mucus - Wan-Rou Lin; Szu-Yu Chen; Shih-Ching Hsiao; Pi-Han Wang (Aerobiologia, 2021)

Biopharmaceutics Applications of Physiologically Based Pharmacokinetic Absorption Modeling and Simulation in Regulatory Submissions to the U.S. Food and Drug Administration for New Drugs - Fang Wu; Heta Shah; Min Li; Peng Duan; Ping Zhao; Sandra Suarez; Kimberly Raines; Yang Zhao; Meng Wang; Ho-pi Lin; John Duan; Lawrence Yu; et al. (The AAPS Journal, 2021)

Shallow gas hydrates off southwest Taiwan and their mechanisms - Yin-Sheng Huang; Shu-Kun Hsu; Chih-Chieh Su; Andrew Tien-Shun Lin; Pai-Sen Yu; Nathalie Babonneau; Gueorgui Ratzov; Serge Lallemand; Pi-Chuen Huang; Shiao-Shan Lin; Jing-Yi Lin; Kuo-Yen Wei; et al. (Marine Geophysical Research, 2021)
We have collected two shallow gas hydrate samples at two sites having different geological settings off southwest Taiwan during the cruise MD214 in 2018. The first core site, MD18-3542, is on the South Yuan-An East Ridge at ~ 1200 m water deep, where a structural unconformity covered by fine-silt sediments appears at ~ 5.5 m below the seafloor. The second core site, MD18-3543, is close to the Good-Weather Ridge at ~ 1100 m water deep, where a gas-related pockmark structure and authigenic carbonates are present at shallow strata with fine-silt sediments near the seafloor. Sediment properties of core MD18-3542 are distinctively different above and below the layer corresponding to the unconformity. Both cores show obvious gaps or voids in the lower core halves. The core features could be linked to the dissociated methane upward migrating from deep strata. Core site settings with upwelling methane would favor the formation of shallow gas hydrates. At site MD18-3542, the shallow hydrate could be formed due to high concentration methane kept beneath the unconformity covered by fine-silt sediments. At site MD18-3543, the shallow hydrate could be formed due to an extremely high flux of upwelling methane trapped either beneath the authigenic carbonates or fine-silt sediments.

Correlation of exosomal microRNA clusters with bone metastasis in non-small cell lung cancer - Xiao-Rong Yang; Can Pi; Ruoying Yu; Xiao-Jun Fan; Xiao-Xiao Peng; Xu-Chao Zhang; Zhi-Hong Chen; Xue Wu; Yang Shao; Yi-Long Wu; Qing Zhou (Clinical & Experimental Metastasis, 2021)
20–40% of lung cancer patients develop bone metastasis (BM) with significantly decreased overall survival. Currently, BM is mainly diagnosed by computerized tomography (CT) scan or magnetic resonance imaging (MRI) when symptom develops. Novel biomarkers with higher prediction value of BM are needed. Plasma-derived exosomal microRNAs had been isolated and sequenced of total 30 non-small cell lung cancer (NSCLC) patients including 16 with bone metastasis and 14 without bone metastasis. Hierarchical clustering based on the total miRNA profile can clearly separate cancer patients and healthy individuals (H), but not patients with (BM +) or without (BM−) BM. Weight Co-expression network of miRNAs (WGCNA) analyses identified three consensus clusters (A, B, C) of highly correlated miRNAs, among which cluster B (144 miRNAs) showed significantly differential expression in lung cancer patients, especially in BM + group. Pathway analysis of cluster B miRNAs revealed enrichment in metabolic pathways that may involve in preconditioning of the metastatic niche. Three differentially expressed miRNAs between BM + and BM− patients within cluster B were identified as miR-574-5p, a suppressor of Wnt/β-catenin pathway, was down-regulated, while miR-328-3p and miR-423-3p, two activators of the same pathway, were up-regulated in BM + patients. Cluster A miRNAs (n = 49) also showed trend of upregulation in BM + patients. Interestingly, pathway analysis indicated that 43 of them are associated with chromosome14, which has been suggested to promote epithelial-mesenchymal transition (EMT) and bone metastasis.

Genome-wide analysis of chloride channel-encoding gene family members and identification of CLC genes that respond to Cl−/salt stress in upland cotton - Xun Liu; Boyi Pi; Jianwei Pu; Cong Cheng; Jiajia Fang; Bingjun Yu (Molecular Biology Reports, 2020)

Influence of near-fault ground motion characteristics on the seismic response of cable-stayed bridges - Chao Zhang; Jian-bing Lu; Hong-yu Jia; Zhi-chao Lai; Xu Li; Pi-guang Wang (Bulletin of Earthquake Engineering, 2020)

Chinese public participation monitoring and warning system for geological hazards - Sheng-nan Wu; Yu Lei; Peng Cui; Rong Chen; Pi-hua Yin (Journal of Mountain Science, 2020)

Paleogeography of South China in the Early Paleozoic: evidence from U–Pb geochronology of detrital monazite - Xiong Yang; Qiaohui Pi; Di Lu; Huidong Yu (Arabian Journal of Geosciences, 2020)

Expression of long pentraxin 3 in human nasal mucosa fibroblasts, tissues, and secretions of chronic rhinosinusitis without nasal polyps - Yih-Jeng Tsai; Chung-Yu Hao; Chih-Li Chen; Pi-Hui Wu; Wen-Bin Wu (Journal of Molecular Medicine, 2020)

Preparation and Characterization of PLGA–PEG–PLGA Nanoparticles Containing Salidroside and Tamoxifen for Breast Cancer Therapy - Xuan Yu; Lili Sun; Lejun Tan; Meng Wang; Xiaoliang Ren; Jiaxin Pi; Miaomiao Jiang; Nan Li (AAPS PharmSciTech, 2020)

How much of Typhoon Morakot's extreme rainfall is attributable to anthropogenic climate change? - Chung‐Chieh Wang; Li‐Shan Tseng; Chien‐Chang Huang; Shih‐How Lo; Cheng‐Ta Chen; Pi‐Yu Chuang; Nan‐Chou Su; K. Tsuboki (International Journal of Climatology, 2019)
Typhoon Morakot (2009), which made landfall in Taiwan during August 7–9, 2009, produced the highest rainfall and became the deadliest typhoon ever recorded in Taiwan since 1958. To assess the role of anthropogenic climate change in the typhoon‐related torrent, we compare the water budget between a pair of cloud‐resolving sensitivity experiments. The pair consists of a control simulation that reproduces Typhoon Morakot (2009) in current climate and a sensitivity simulation in which the same storm is placed in a slightly different climate background where the late 20th century anthropogenic climate change signal is removed. The anthropogenic signal is estimated with the CMIP5 experiments of 18 models for the period of 1985–2005, during which the global warming trend is discernible. In climate states that differ merely by a 20‐year mean anthropogenic change, Morakot (2009) yields 3.4–3.6% more total rainfall in the control experiment than its sensitivity counterpart within a radius of 300–500 km from the storm centre. Water budget analysis indicates that the increase in typhoon rainfall is mainly resulted from the enhanced convergence of vapour flux. The enhancement is, in turn, contributed by the increased tropospheric moisture due to global warming and, to a lesser extent, by a more active secondary circulation in the storm that is associated with the anthropogenic climate change.

Biota-sediment metal accumulation and human health risk assessment of freshwater bivalve Corbicula fluminea in Dongting Lake, China - Deliang Li; Jian Wang; Jie Pi; Jianbo Yu; Ting Zhang (Environmental Science and Pollution Research, 2019)

Sonodynamic Therapy on Intracranial Glioblastoma Xenografts Using Sinoporphyrin Sodium Delivered by Ultrasound with Microbubbles - Zhaoke Pi; Yongpeng Huang; Yuanyuan Shen; Xiaojun Zeng; Yaxin Hu; Tie Chen; Chenyang Li; Hao Yu; Siping Chen; Xin Chen (Annals of Biomedical Engineering, 2019)

Gender differences and lung cancer risk in occupational chefs: analyzing more than 350,000 chefs in Taiwan, 1984–2011 - Pei-Chen Lin; Chiung-Yu Peng; Chih-Hong Pan; Pi-I Debby Lin; Ming-Tsang Wu (International Archives of Occupational and Environmental Health, 2019)

Sodium Metabisulfite: Effects on Ionic Currents and Excitotoxicity - Ming-Chi Lai; Te-Yu Hung; Kao-Min Lin; Pi-Shan Sung; Shyh-Jong Wu; Chih-Sheng Yang; Yi-Jen Wu; Jing-Jane Tsai; Sheng-Nan Wu; Chin-Wei Huang (Neurotoxicity Research, 2018)

Mass spectrometry-guided isolation of two new dihydrobenzophenanthridine alkaloids from Macleaya cordata - Zhi-Xing Qing; Peng Yang; Kun Yu; Xue-Yi Yang; Jing-Hong Liu; Feng Xiang; Hua-Liang Cao; Pi Cheng; Jian-Guo Zeng (Natural Product Research, 2017)

Response of Selenium and Selenogenome in Immune Tissues to LPS-Induced Inflammatory Reactions in Pigs - Lv-Hui Sun; Ding-An Pi; Ling Zhao; Xiu-Ying Wang; Luo-Yi Zhu; De-Sheng Qi; Yu-Lan Liu (Biological Trace Element Research, 2017)

Evaluation of the Therapeutic Effects of Hyaluronic Acid Injections on Football Players’ Articular Cartilage Using an Immunochromatographic Urine Strip - Chun-Shien Wu; Hsia-Ying Cheng; Pi-Fong Hsu; Yu-Hsien Kao; Shyh Ming Kuo (Journal of Medical and Biological Engineering, 2017)

The critical role of ABCG1 and PPARγ/LXRα signaling in TLR4 mediates inflammatory responses and lipid accumulation in vascular smooth muscle cells - Xiaojie Cao; Lili Zhang; Chunhai Chen; Qingsong Wang; Lu Guo; Qinlong Ma; Ping Deng; Gang Zhu; Binghu Li; Yan Pi; Chunyan Long; Lei Zhang; et al. (Cell and Tissue Research, 2017)

Genomic and transcriptome analysis of triclosan response of a multidrug-resistant Acinetobacter baumannii strain, MDR-ZJ06 - Borui Pi; Dongliang Yu; Xiaoting Hua; Zhi Ruan; Yunsong Yu (Archives of Microbiology, 2017)

Research on China export structure adjustment: an embodied carbon perspective - Pi-qin Gong; Bao-jun Tang; Yu-chong Xiao; Gao-jie Lin; Jian-yun Liu (Natural Hazards, 2016)

Hispidulin alleviated methamphetamine-induced hyperlocomotion by acting at α6 subunit-containing GABAA receptors in the cerebellum - Yu-Hsiang Liao; Hsin-Jung Lee; Wei-Jan Huang; Pi-Chuan Fan; Lih-Chu Chiou (Psychopharmacology, 2016)

Abrp, a new gene, confers reduced susceptibility to tetracycline, glycylcine, chloramphenicol and fosfomycin classes in Acinetobacter baumannii - X. Li; J. Quan; Y. Yang; J. Ji; L. Liu; Y. Fu; X. Hua; Y. Chen; B. Pi; Y. Jiang; Y. Yu (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

USPIO assisting degradation of MXC by host/guest-type immobilized laccase in AOT reverse micelle system - Yu-Xiang Yang; Na Pi; Jian-Bo Zhang; Yan Huang; Ping-Ping Yao; Yan-Jie Xi; Hong-Ming Yuan (Environmental Science and Pollution Research, 2016)

Mass spectrometry-guided isolation of two new benzoquinoline alkaloids from Macleaya cordata - Zhi-Xing Qing; Yu-Qin Xu; Peng Yang; Kun Yu; Pi Cheng; Jian-Guo Zeng (Natural Product Research, 2016)

Proteomic changes induced by potassium deficiency and potassium substitution by sodium in sugar beet - Zhi Pi; Piergiorgio Stevanato; Fei Sun; Yun Yang; Xuewei Sun; Huijie Zhao; Gui Geng; Lihua Yu (Journal of Plant Research, 2016)

Age polyethism drives community structure of the bacterial gut microbiota in the fungus‐cultivating termite O dontotermes formosanus - Hongjie Li; Carsten Dietrich; Na Zhu; Aram Mikaelyan; Bin Ma; Ruoxi Pi; Yu Liu; Mengyi Yang; Andreas Brune; Jianchu Mo (Environmental Microbiology, 2016)
Summary Fungus‐cultivating termites ( M acrotermitinae) possess an elaborate strategy of lignocellulose digestion. It involves a lignocellulose‐degrading fungal symbiont (genus T ermitomyces ), a diverse gut microbiota and a characteristic labour division in food processing. In this study, using pyrotag sequencing and electron microscopy, we analysed the bacterial microbiota in the hindgut of O dontotermes formosanus and its fungus comb to investigate the spatial organization, establishment and temporal succession of the bacterial communities colonizing specific microhabitats. Our results document strong differences between the communities at the hindgut epithelium and the luminal fluid of newly moulted, young and old worker termites. The differences in community structure were consistent with the density, morphology and spatial distribution of bacterial cells and the pools of microbial metabolites in the hindgut compartment, underlining that both gut development and the age‐specific changes in diet affect the composition and functional role of their gut microbiota. These findings provide strong support for the concept that changes in diet and gut environment are important determinants of community structure because they create new niches for microbial symbionts.

Association of polygalacturonase-inhibiting protein gene 2 (MsPGIP2) to common leaf spot resistance in alfalfa - Zhi Gui; Jianming Gao; Nan Xin; Yu Wang; Yongshuo Pi; Huiqin Liu; Qinghua Yuan; Xianglin Li (European Journal of Plant Pathology, 2016)

Numerical Simulation of Response Characteristics of Audio-magnetotelluric for Gas Hydrate in the Qilian Mountain Permafrost, China - Kun Xiao; Changchun Zou; Changqing Yu; Jinyun Pi (Acta Geophysica, 2015)

Effectiveness of soil conservation methods in preventing red soil erosion in Southern China - Guo-Hua Zhang; Chong-Bao Xie; Xiao-Yu Pi; Chang-Qing Zuo (Journal of Mountain Science, 2015)

A new naphthalenone isolated from the green walnut husks of Juglans mandshurica Maxim. - Guang Chen; Xin-Mei Pi; Chang-Yuan Yu (Natural Product Research, 2015)

Effects of elevated CO2 and temperature on the growth, elemental composition, and cell size of two marine diatoms: potential implications of global climate change - Kwee Siong Tew; Yu-Chen Kao; Fung-Chi Ko; Jimmy Kuo; Pei-Jie Meng; Pi-Jen Liu; David C. Glover (Hydrobiologia, 2014)

Genetic diversity and identification of race 3 of Fusarium oxysporum f. sp. lactucae in Taiwan - Ying-Hong Lin; Po-Jung Lai; Tao-Ho Chang; Yu-Ling Wan; Jenn-Wen Huang; Jin-Hsing Huang; Pi-Fang Linda Chang (European Journal of Plant Pathology, 2014)

Synthesis and anti-cancer activity of a glycosyl library of $$\varvec{N}$$ N -acetylglucosamine-bearing oleanolic acid - Yi-Bing Zeng; Hsin-Min Hsiao; She-Hung Chan; Ying-Hsin Wang; You-Yu Lin; Yu-Hsuan Kuo; Jih-Hwa Guh; Pi-Hui Liang (Molecular Diversity, 2014)

Amino Acid, Fatty Acid, and Metal Compositions in Edible Parts of Three Cultured Economic Crabs: Scylla paramamosain, Portunus trituberculatus , and Eriocheir sinensis - Ke-Ji Jiang; Feng-Ying Zhang; Yan Pi; Li-Li Jiang; Zhong-Li Yu; Dan Zhang; Man-Man Sun; Lu-Jiao Gao; Zhen-Guo Qiao; Ling-Bo Ma (Journal of Aquatic Food Product Technology, 2014)

A molecular diagnosis method using real-time PCR for quantification and detection of Fusarium oxysporum f. sp. cubense race 4 - Ying-Hong Lin; Ching-Chung Su; Chih-Ping Chao; Chi-Yu Chen; Chung-Jan Chang; Jenn-Wen Huang; Pi-Fang Linda Chang (European Journal of Plant Pathology, 2013)

Polysaccharides purified from the submerged culture of Ganoderma formosanum stimulate macrophage activation and protect mice against Listeria monocytogenes infection - Cheng-Li Wang; Chia-Chen Pi; Chu-Wei Kuo; Yu-Jing Zhuang; Kay-Hooi Khoo; Wen-Hsiung Liu; Chun-Jen Chen (Biotechnology Letters, 2011)

An intelligent electronic capsule system for automated detection of gastrointestinal bleeding - Hong-ying Liu; Gang Wang; Kang Wei; Xi-tian Pi; Lan Zhu; Xiao-lin Zheng; Zhi-yu Wen (Journal of Zhejiang University-SCIENCE B, 2010)

Establishment and characterization of an osteopontin-null cutaneous squamous cell carcinoma cell line - Yu-Hua Hsieh; M. Margaret Juliana; Pi-Ling Chang (In Vitro Cellular & Developmental Biology - Animal, 2010)

A new flavonol galloylrhamnoside and a new lignan glucoside from the leaves of Koelreuteria henryi Dummer - Tzong-Huei Lee; Yuan-Hsiang Chiang; Chin-Hui Chen; Pi-Yu Chen; Ching-Kuo Lee (Journal of Natural Medicines, 2009)

A population-based, case–control study of green tea consumption and leukemia risk in southwestern Taiwan - Yau-Chang Kuo; Chu-Ling Yu; Chen-Yu Liu; Su-Fen Wang; Pi-Chen Pan; Ming-Tsang Wu; Chi-Kung Ho; Yu-Shing Lo; Yi Li; David C. Christiani (Cancer Causes & Control, 2009)